In silico structure modeling and specifitify analysis of DehD Dehalogenase from Rhizobium sp. RCI - Ismaila Yada Sudi, 1964-, author 600747; Fahrul Huyop, supervisor 615254; Shahir Shamsir, supervisor; Haryati Jamaluddin, supervisor 601462; Fakulti Biosains dan Kejuruteraan Perubatan 538915 (2014)
Thesis (Ph.D (Biosains)) - Universiti Teknologi Malaysia, 2014